The Aegean and the Orient in the Second Millennium B. C. - Kantor, Helene J.
1. The First Expansion of Aegean Commerce (The Distribution of Middle Minoan Objects in the Orient. The Appareance of Spiraliform Ornament in Egypt. Spiraliform Ornament in Asia) — 2. The Second Phase of Aegean Relations with the East (Aegean Pottery of the Late Bronze I and II Ages in the East. The Contribution of Oriental Evidence to the Controversy over Cretan-Mainland Relations) — 3. The Influence of the Aegean upon the Arts of Egypt and Western Asia in the Late Bronze I and II Ages (Egypt, Asia) — 4. Late Helladic III Commerce and Its Effect upon the Art of the Near East (Late Mycenaean Trade. LH III Influence in Egyptian Art. The Art of the LH III Period in Asia) — Conclusion.